The reservoir of latent HIV - Chen, Jing; Zhou, Tong; Zhang, Yuan; Luo, Shumin; Chen, Huan; Chen, Dexi; Li, Chuanyun; Li, Weihua (Frontiers in Cellular and Infection Microbiology, 2022)
The persistence of latent reservoir of the human immunodeficiency virus (HIV) is currently the major challenge in curing HIV infection. After HIV infects the human body, the latent HIV is unable to be recognized by the body’s immune system. Currently, the widely adopted antiretroviral therapy (ART) is also unble to eliminate it, thus hindering the progress of HIV treatment. This review discusses the existence of latent HIV vault for HIV treatment, its formation and factors affecting its formation, cell, and tissue localization, methods for detection and removing latent reservoir, to provide a comprehensive understanding of latent HIV vault, in order to assist in the future research and play a potential role in achieving HIV treatment.